2022
DOI: 10.47176/mjiri.36.58
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Calcium Score and Conventional Risk Factors in the Diagnosis of Atherosclerosis

Abstract: The CAC score is a well-established marker of coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 21 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…In our study, according to the Agatston calcium score, coronary artery calcification was present in 111 (50%) of the patients, similar to other studies in the scientific literature, where the CCTA revealed that approximately 40-55.4% of the studied patients had a positive CAC score [12,13], but there have been studies reporting a higher prevalence of CAC score of up to 70% [15].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, according to the Agatston calcium score, coronary artery calcification was present in 111 (50%) of the patients, similar to other studies in the scientific literature, where the CCTA revealed that approximately 40-55.4% of the studied patients had a positive CAC score [12,13], but there have been studies reporting a higher prevalence of CAC score of up to 70% [15].…”
Section: Discussionsupporting
confidence: 89%
“…The CAC score is a marker directly related to known atherosclerosis risk factors that correlate well with atherosclerotic plaque burden and can be accurately assessed via computed tomography using the Agatston calcium score compared to other cardiac risk factors-based paradigms [1,5,13,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Church et al conducted a study on conventional risk factors and their association with CAC score and reported hypertension in 9% of patients having a CAC score <100 and in 16% of patients having a CAC score ≥100, smoking history in 5% of patients having a CAC score <100 and in 5% patients having a CAC score ≥100, and diabetes mellitus in 5% patients having a CAC score <100 and in 9% patients having a CAC score ≥100. [11] Our study is in contradiction with the study conducted in Iran by Yazdi et al We were unable to establish a strong association between conventional risk factors and CAC score, but Yazdi et al revealed that a non-zero CAC score is strongly associated with the conventional risk factors of ischemic heart disease [12].…”
Section: Discussioncontrasting
confidence: 89%